Plant Phenotypic Plasticity in Response to Environmental Factors - Gratani, Loretta (Advances in Botany, 2014)
Plants are exposed to heterogeneity in the environment where new stress factors (i.e., climate change, land use change, and invasiveness) are introduced, and where inter- and intraspecies differences may reflect resource limitation and/or environmental stress factors. Phenotypic plasticity is considered one of the major means by which plants can cope with environmental factor variability. Nevertheless, the extent to which phenotypic plasticity may facilitate survival under environmental condition changes still remains largely unknown because results are sometimes controversial. Thus, it is important to identify plant functional traits in which plasticity may play a determinant role in plant response to global change as well as on the ecological consequences at an ecosystem level for the competition between wild and invasive species, considering that species with a greater adaptive plasticity may be more likely to survive in novel environmental conditions. In the near future, it will be important to increase long-term studies on natural populations in order to understand plant response to environmental factor fluctuations including climate change. There is the necessity to analyze variations at phenotypic and genetic levels for the same species and, in particular, for endemic and rare species because these could have drastic effects at an ecosystem level.